Compression‐refractory breast hematoma secondary to pseudoaneurysm after stereotactically guided vacuum‐assisted biopsy: The critical role of urgent surgical evacuation. Issue 8 (3rd July 2014) - Sun, Simon; Hennessey, Hooman; Kam Nakch, Idris; Alsharif, Shaza; Meterissian, Sarkis; Mesurolle, Benoît
ABSTRACT We report the case of a patient who underwent a vacuum‐assisted biopsy of amorphous clustered microcalcifications complicated by a large compression‐refractory hematoma secondary to pseudoaneurysm formation. Breast sonography was used to identify an actively bleeding vessel and guide compression. However, due to its unresponsiveness to conventional management and rapid progression, the hematoma required surgical evacuation and ligation of the bleeding vessel. This suggests that, in the face of significant intractable bleeding, a heightened awareness of the possible need for surgical intervention should be maintained. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:492–494, 2014